Comparison of Student Learning Outcomes in Class VIII SMP Negeri 2 Muaro Jambi - Neny Juharti; Lia Kartina (Cahaya Ilmu Cendekia Publisher, 2021)
Purpose of the study: Knowing the comparison of student learning outcomes in grade 8 at SMP Negeri 2 Muaro Jambi based on the level of work character of the students. Methodology: This study is a quantitative study, the study was conducted at SMP Negeri 2 Muaro Jambi Regency, the sample of the study was students of class VIII, data collection used a hard work questionnaire while the learning outcomes used question instruments. Main Findings: Character education has a positive influence on student learning outcomes. One of the important characters is the character of hard work. Hard work character is a character to use all abilities to achieve maximum results. Based on research conducted on 58 students at State Middle School 2 Muaro Jambi, to determine the relationship between the character of hard work and student learning outcomes. Obtained character hard work has a positive impact on student learning outcomes. So the teacher can help students to be able to foster the character of hard work in each student. Moreover, the current curriculum puts forward character education. The teacher can give the character growth of hard work by providing examples of successful people who have a great will and work hard even though they do not have more ability to realize their dreams. Likewise in Islam, good character education can have an impact on all aspects of activities not only in the academic field but also in the non-academic field. Novelty / Originality of this study: This study is the first to be conducted at a public junior high school in Muaro Jambi district to determine the comparison of student learning outcomes based on student learning outcomes.